An Introduction to Kolmogorov Complexity and Its Applications - Li, Ming (Texts in Computer Science, 2008)
Written by two experts in the field, this is the only comprehensive and unified treatment of the central ideas and applications of Kolmogorov complexity. The book presents a thorough treatment of the subject with a wide range of illustrative applications.